Development of Character-Based Comic Media to Improve Learning Outcomes of Mathematics Subjects in Elementary Schools - Harianti Hatta; Masnur Masnur; Nadar Nadar (Edumaspul: Jurnal Pendidikan, 2024)
This research aims to develop character-based comic media to improve mathematics learning outcomes of elementary school students, specifically on multiplication material in third grade. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. Research subjects included 90 third-grade students and 6 mathematics teachers from three elementary schools in Parepare City, South Sulawesi. Research instruments consisted of validation sheets, practicality questionnaires, learning outcome tests, learning implementation observation sheets, and interview guidelines. Data analysis techniques included descriptive analysis for qualitative data and correlated t-test and N-gain calculation for quantitative data. The results showed that: (1) Character-based comic media has been successfully developed following the ADDIE model and adapted to the characteristics of third-grade elementary school students; (2) Comic media was rated as very valid by material experts (4.58), media experts (4.67), and character education experts (4.52); (3) Comic media was rated as very practical by teachers (88.4%) and students (87.6%); (4) Comic media proved effective in improving students' mathematics learning outcomes with a significant increase from pretest (54.67) to posttest (82.44) with an N-gain of 0.61 (medium category); (5) There was an increase in the internalization of character values in students from an average score of 2.73 to 3.61; (6) Teacher and student responses to comic media were in the very positive category with percentages of 92.2% and 90.4%. The novelty of this research lies in the integration of digital technology in the development of character-based mathematics comics that can be accessed through mobile applications, as well as the explicit integration of character values in mathematics learning. The results of this research can be an alternative solution to improve mathematics learning outcomes while instilling character values in elementary school students